1998
DOI: 10.1159/000013337
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect of Gemfibrozil on Cyclosporine Blood Concentrations in Kidney-Transplanted Patients

Abstract: Forty kidney-transplanted patients with hypertriglyceridemia, under treatment with cyclosporine alone or associated with other immunosuppressive drugs, were treated with gemfibrozil. This drug, for a long-term treatment (ranging from 4 to 6 months), was able to decrease hypertriglyceridemia and did not modify either polyclonal (P) and monoclonal (M) cyclosporine blood levels or P/M ratio. These data seem to exclude an effect of gemfibrozil on cyclosporine blood concentrations. Therefore, the use of gemfibrozil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Studies of fibrate class drugs have shown that neither gemfibrozil nor fenofibrate alters cyclosporine levels and therefore do not require modification of cyclosporine doses (60, 61). Ezetemibe also does not affect levels of cyclosporine, tacrolimus, sirolimus or mycophenolate mofetil and can therefore be safely used with these immunosuppressive therapies (54).…”
Section: Hyperlipidaemiamentioning
confidence: 99%
“…Studies of fibrate class drugs have shown that neither gemfibrozil nor fenofibrate alters cyclosporine levels and therefore do not require modification of cyclosporine doses (60, 61). Ezetemibe also does not affect levels of cyclosporine, tacrolimus, sirolimus or mycophenolate mofetil and can therefore be safely used with these immunosuppressive therapies (54).…”
Section: Hyperlipidaemiamentioning
confidence: 99%
“…In addition to pathophysiological causes (kidney diseases, obesity, diabetes) [1,10], it has been also reported that the administration of Cs-A and steroids, used as immunosuppressive agents in organ-transplanted patients, is responsible for hyperlipidemia [11][12][13]. The hypothesized mechanisms by which these drugs increase cholesterol and triglyceride serum concentrations have been described in our previous study [8]. According to the European Atherosclerosis Society, hyperlipidemia was treated with two HMG-CoARIs, simvastatin and pravastatin [9].…”
Section: Discussionmentioning
confidence: 82%
“…On the basis of these evidences, several authors [5][6][7][8] suggested treatment of hyperlipidemia with lipid-lowering drugs in organ transplant recipients to prevent these risks.…”
Section: Introductionmentioning
confidence: 99%
“…47 Data demonstrating potential drug interaction between gemfibrozil or fenofibrate and CSA are conflicting. 48 Studies suggest an 18% to 27% reduction in CSA trough levels with concomitant fibric acid use. 49,50 Although reports of myotoxicity with CSA are few, the potential exists.…”
Section: Antihypertensivesmentioning
confidence: 99%